2016
DOI: 10.1002/mrm.26151
|View full text |Cite
|
Sign up to set email alerts
|

Safety and technique of ferumoxytol administration for MRI

Abstract: Ferumoxytol is an ultrasmall superparamagnetic iron oxide agent marketed for the treatment of anemia. There has been increasing interest in its properties as an MRI contrast agent as well as greater awareness of its adverse event profile. This mini-review summarizes the current state of knowledge of the risks of ferumoxytol and methods of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
164
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 183 publications
(166 citation statements)
references
References 51 publications
1
164
1
Order By: Relevance
“…In practice, it was challenging to run both approaches in the same patients because that would require two separate imaging sessions. Guidelines for Ferumoxytol administration at our institution require that the USPIO contrast should be slowly infused in the nursing station under close monitoring [16]. However, the two groups studied were roughly equal in size, age, and indication for imaging (mainly aortic valve replacement and aortic dilation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, it was challenging to run both approaches in the same patients because that would require two separate imaging sessions. Guidelines for Ferumoxytol administration at our institution require that the USPIO contrast should be slowly infused in the nursing station under close monitoring [16]. However, the two groups studied were roughly equal in size, age, and indication for imaging (mainly aortic valve replacement and aortic dilation).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous publication, we found USPIO MRA had comparable measurement of aortic annulus area with trans-esophageal echocardiography (TEE) as the gold standard using a similar 3D MRA protocol [8]. The blood pool contrast agent used (ferumoxtyol) has a higher reported incidence of anaphylaxis than gadolinium (1:10,000) [16]. We followed the recommended safety precautions to minimize the risk of allergic reaction, including the slow infusion of contrast in the nursing holding area with continuous monitoring before the MRI, and also obtained consent prior to contrast administration [16].…”
Section: Discussionmentioning
confidence: 99%
“…For a translational approach, toxicity assessments should be performed on case by case basis. A number of clinical safety issues of clinical approved SPIO have been described, thought the incidence is overall uncommon (14)(15)(16)(17)(18)(19). Importantly, SPIO is not indicated in pregnant women.…”
Section: A B C D E C B Amentioning
confidence: 99%
“…There has been great interest in using USPIO contrast agents due to lack of renal excretion and absence of NSF risk; however, initial postmarket studies in adults have reported a risk of cardiac adverse events and anaphylaxis that is higher than with GBCA (26). In addition, these agents are taken up by the reticuloendothelial system and are retained for weeks to several months and may lead to an additional risk of iron overload with repeat doses.…”
Section: Mri Risksmentioning
confidence: 99%